Resonanzen des Tragischen Zwischen Ereignis und Affekt - Haitzinger, Nicole (Turia und Kant, 2015)
This study is dedicated to the notion of the tragic in European dance theatre, the evocation of which takes place in a field of tension constituted by staging techniques as well as by conceptions, procedures and moments of interruption, of suspension, of disturbance and of an indeterminability effected by ec-static corporeality. It is possible to recognise in the event-generating structure and function of the tragic formal principles and an aesthetics of effect coupled to new constellations of the fictional and the choric, absence and presence. From the perspective of dance studies, the tragic emerges from the representation by means of the moving and moved body of a gruesome monstrosity at the limits of what is imaginable; but how exactly does the mise-en-scène of the ambivalent, ambiguous and paradoxical through figures and figurations of pathos function to make the tragic appear?